O resgate dos começos (sensíveis) perdidos: a dimensão sensível do cuidado na clínica psicanalítica com crianças e seus pais numa perspectiva entre a teologia, a fenomenologia da vida e a psicanálise - Bangel, Marina Lucia Tambelli (2015)
This study, inserted in the line of research Dimensions of Care and Social Practices, has as its theme affectivity. It stems from changes observed in clinical work and in the schools, as well as in daily life, to introduce the lack of care as neglect disregard and abandonment of the sensitive life due to the modern paradigm, an issue which theology, phenomenology of Life and psychoanalysis coincide in denouncing. From this starting point the study investigates Michel Henry s criticism of the modern world, as well as the recovery of affectivity which the author proposes based on the lost beginning in Descartes. Through this, thinking is anchored as a sensitive knowledge, guided by feeling oneself, which would permit indicating points of approximation between the phenomenology of Life and psychoanalysis based on the concepts of Life and pulsion as well as of the relation between the living. In the second chapter the theme of the beginning is dealt with from the perspective of the biblical narrative as well as from the psychoanalytical clinical perspective. These theoretical resources, from the perspective of theology, phenomenology of Life and psychoanalysis, having as their guiding thread care, considered in this study as a constant affective involvement of oneself (based on feeling oneself) with the other/the different (based on feeling), will serve as a base from which to point out possible contributions for clinical treatment, related to a snipping coming from lack of limits / hyperactivity as one of the manifestations of infant suffering through the body, with children and their parents based on the recovery of lost (sensitive) beginnings.